المظهر العمراني الشرشالي في النصف الثاني من القرن 19 م وبداية القرن20 م من خلال وثائق المحاكم الشرعية - بحيري يامنة (University Of Eloued جامعة الوادي, 2023)
لقد ميّز مدينة شرشال نسيج عمراني خاص أدلت به الوثائق و أفادت في التعرّف على أهم منشآته الحضارية الإسلامية و مواقعها و مختلف معالمها، فالبناءات الأوروبية الجديدة و الأحياء المستحدثة أدّت إلى تحطيم بنى العمران الخاص بالمدينة، و الذي يعكس خصوصيّة أهلها من ثقافة و دين و تقاليد و عادات، و إحلال محله هندسة معمارية أوروبية جديدة، وعليه فقد أصبح من المؤكد أن البحث في المظهر العمراني من عمارة مدنية وعمومية في المنطقة أثناء مرحلة حساسة من تاريخ الجزائر يثير العديد من التساؤلات التاريخية، مما جعلها محل البحث والدراسة. فهذه الدراسة تبرز الطابع العمراني و المعماري لمدينة شرشال في هذه الفترة، و كيف تصوره لنا الوثائق الشرعية؟ فما هي أبعد نقطة أوصلتنا إليها الوثائق لرسم صورة العمران، و خصوصية العمارة الموريسكية و العثمانية قبل زلزلة الإحتلال الفرنسي لها بالمنشآت الأوروبية؟. Cherchell has been recognized by a special urban fabric ,that was provided by documents that help to identify it through the most important civilizational facilities , and its sites and also its various features So modern European architectures lead to the destruction of the urban structures of the City, which reflects the privacy of its people through culture , religion, and customs ,replaced by modern European architect So it has become certain that research in urban appearance during civil and public buildings in the region through a sensitive period of Algerian History and this raises a number of historical questions which made it the subject of research and study. This study highlights the urban and the architectural character of cherchell 's City during that period And how the legal documents portray it to us ?what is the farthest point to which the documents brought us to draw a picture of urbanization and the specifity of the Moorish and Ottoman architecture before the earthquake of the French Occupation through European facilities
Keywords: شرشال; نسيج عمراني; وثائق; المحاكم الشرعية; القرن 19 بداية القرن 20م; Cherchell; urban fabric; Documents; Sharia courts; 19th Century early 20th Century AD